On a collection of brachyuran crabs from Lakshadweep, Indian Ocean (Crustacea: Decapoda: Brachyura) - Devi, S. Suvarna; Mendoza, Jose C. E.; Ravinesh, R.; Babu, K. K. Idress; Kumar, A. Biju; Ng, Peter K. L. (Zootaxa, 2019)
The crab fauna (Crustacea: Brachyura) of Lakshadweep (Laccadives), a group of Indian islands in the western Indian Ocean is updated, using material from the intertidal and shallow subtidal areas collected between 2012 and 2015. Fifty-three species were recorded during this study, of which 17 species are newly recorded from the islands, and three are also new records for India. A total of 169 species of brachyuran crabs are now known from Lakshadweep. The taxonomy of Elamena gracilis Borradaile, 1903 (Hymenosomatidae) is clarified and stabilized by the designation of a lectotype.